Pengaruh Strategi Talent Management dan Keterlibatan Karyawan terhadap Retensi Karyawan Perumda Tirta Kahuripan Kabupaten Bogor - Nadiva Zalza Aulia; Azis Firdaus; Hartanti Nugrahaningsih (Global Leadership Organizational Research in Management, 2025)
Employee engagement and talent management methods' impact on Perumda Tirta Kahuripan Bogor Regency's retention rates is the primary research objective of this study. The high turnover rate is the company's biggest issue since it threatens the long-term viability of the business. The study team at Perumda Tirta Kahuripan used a quantitative approach by surveying 70 workers to gather data. Both basic and multivariate linear regression were used to evaluate the data. The findings demonstrated that talent management and employee engagement both contribute to a more loyal workforce and boost retention rates. According to the modified R-squared value of 58.7%, the effect on employee retention can be explained by 58.7% by combining the factors of talent management and employee engagement. The remaining portion is impacted by variables that were not included in this research. In order to keep a competent staff and loyal customers, these results show that talent management and enhanced employee engagement are crucial.